2004
DOI: 10.1097/01.inf.0000115631.99896.41
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A virus-associated acute necrotizing encephalopathy in the United States

Abstract: During the past several years, influenza-associated acute necrotizing encephalopathy has been well-recognized in Asia but has not yet been reported in the United States. We describe a 28-month-old patient who displayed the classical clinical features of acute necrotizing encephalopathy in association with a documented influenza A infection. This disease is characterized by fever, a rapid alteration in consciousness and seizures, with radiologic involvement of the bilateral thalami and cerebellum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
2
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 20 publications
(22 reference statements)
2
44
2
2
Order By: Relevance
“…Although the use of ECMO in patients with 2009 H1N1 influenza infection has been less extensively studied, uniformly fatal intracranial hemorrhage has been described in one case series [3]. Intracranial hemorrhage can also occur in the setting of influenza-associated encephalopathy, often accompanied by multi-organ failure, disseminated intravascular coagulation, and diffuse cerebral edema [6,7]. This well-described neurological complication of influenza infection makes it difficult to determine with certainty whether the pathogenesis of intracranial hemorrhage in critically ill patients with H1N1 influenza infection undergoing ECMO is a result of influenza-related vascular injury, an underlying hemorrhagic diathesis secondary to hypercytokinemia-associated thrombocytopenia and elevated prothrombin time, an adverse effect of ECMO, anticoagulation required for ECMO, or some combination thereof.…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of ECMO in patients with 2009 H1N1 influenza infection has been less extensively studied, uniformly fatal intracranial hemorrhage has been described in one case series [3]. Intracranial hemorrhage can also occur in the setting of influenza-associated encephalopathy, often accompanied by multi-organ failure, disseminated intravascular coagulation, and diffuse cerebral edema [6,7]. This well-described neurological complication of influenza infection makes it difficult to determine with certainty whether the pathogenesis of intracranial hemorrhage in critically ill patients with H1N1 influenza infection undergoing ECMO is a result of influenza-related vascular injury, an underlying hemorrhagic diathesis secondary to hypercytokinemia-associated thrombocytopenia and elevated prothrombin time, an adverse effect of ECMO, anticoagulation required for ECMO, or some combination thereof.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that this patient's second presentation is best explained as influenza-associated ANE, representing only the second such report from the United States. 30 The only other associated infectious finding was the isolation of adenovirus in the child's stool at the second presentation. It is interesting that Steininger et al 14 reported a possible association between adenoviral infection and postinfluenzal encephalopathy after influenza A virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…ANE demonstrates clinical and laboratory test findings different from these diseases; nonetheless, recognition of typical neuroradiologic features is extremely important to correctly diagnose this rare encephalopathy frequently associated with high mortality and morbidity. 11 Radiologists should become aware of the central role of MR imaging in aiding clinicians to formulate a presumptive diagnosis of ANE and, therefore, initiate appropriate treatment. The importance of this imaging technique, eventually associated with DTI, should be advocated as well in the follow-up of these patients to guide the clinical approach and predict the final outcome.…”
Section: Discussionmentioning
confidence: 99%